2017
DOI: 10.1002/rse2.68
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic use of Sentinel‐1 and Sentinel‐2 for assessments of heathland conservation status

Abstract: Habitat quality assessments often demand wall-to-wall information about the state of vegetation. Remote sensing can provide this information by capturing optical and structural attributes of plant communities. Although active and passive remote sensing approaches are considered as complementary techniques, they have been rarely combined for conservation mapping. Here, we combined spaceborne multispectral Sentinel-2 and Sentinel-1 SAR data for a remote sensing-based habitat quality assessment of dwarf shrub hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…The open data policy of Landsat and Sentinel potentially allows for such an approach, and recently published datasets aiming at capturing forest cover dynamics and human disturbance (Hansen et al, ) provide starting points to explore this approach. Further, the free, global availability of Sentinel‐1 SAR data potentially enable the assessment and incorporation of vegetation structural attributes (Schmidt et al, ) into large‐scale assessments and analyses of insect communities. Though there have been several promising studies that showed correlations between remote sensing products and ecosystem structure, habitat conditions, and animal communities, it must be acknowledged that we are still in an early stage of deriving reliable indicators for biodiversity information from earth observation data (Bush et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The open data policy of Landsat and Sentinel potentially allows for such an approach, and recently published datasets aiming at capturing forest cover dynamics and human disturbance (Hansen et al, ) provide starting points to explore this approach. Further, the free, global availability of Sentinel‐1 SAR data potentially enable the assessment and incorporation of vegetation structural attributes (Schmidt et al, ) into large‐scale assessments and analyses of insect communities. Though there have been several promising studies that showed correlations between remote sensing products and ecosystem structure, habitat conditions, and animal communities, it must be acknowledged that we are still in an early stage of deriving reliable indicators for biodiversity information from earth observation data (Bush et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, accuracy greater than 85% could be reached only by using airborne hyperspectral (Burai, Deák, Valkó, & Tomor, ), hyperspatial resolution imagery from an unmanned aerial vehicle (Kaneko & Nohara, ) or full‐waveform LiDAR data (Launeau et al., ) of small sites covering several hectares. However, the new Sentinel time‐series with a high spatial resolution (10 m) seems promising to accurately map natural habitats, using Sentinel‐1 SAR (Schmidt, Fassnacht, Förster, & Schmidtlein, ) or Sentinel‐2 multispectral (Shoko & Mutanga, ) sensors. Such time‐series satellite images, which are both free and cost‐effective, are now available and appear promising to accurately distinguish between plant communities in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used RS data to map nine “elementary” habitats that are included in the “thermo‐Atlantic and sub‐brackish meadows” Natura 2000 habitat, which encompasses diverse and even contrary environmental conditions caused by environmental management such as flood duration (from less than 1 month for Hordeo secalini‐Lolietum perennis up to 4 months for Eleocharito palustris‐Oenanthetum fistulosae ) and agricultural practices (grazing for Carici divisae‐Lolietum perennis or mowing for Junco gerardi‐Oenanthetum fistulosae ). From a structural perspective, each “elementary” habitat that we mapped could be used as a surrogate for a species pool (Zlinszky et al., ) but also for species richness, stand structural diversity or key species cover (Neumann et al., ; Schmidt et al., ). From a functional perspective, these “elementary” habitats—which are ecologically homogeneous units—could also provide insights into their corresponding environmental conditions as well as their functional traits (e.g., seed mass), which are indirectly detectable from RS data (Violle et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the area, the training polygons occupied from 0.01% to 0.07% of the surveyed area (calculated area covered by the target species polygons). It can therefore be assumed that a set of polygons, optimized in terms of the percentage cover of a species, allows for a correctly assessed classification with a significantly lower sampling rate compared to 1–2% of the area described in the literature [59]. The correct result of identification on a comparable set of training polygons was achieved with the use of the Mixture Tuned Matched Filtering (MTMF) algorithm [58] when mapping Cardaria draba .…”
Section: Discussionmentioning
confidence: 99%